1995
DOI: 10.1002/art.1780380814
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the american college of rheumatology recommendations for liver biopsy in methotrexate‐treated rheumatoid arthritis patients

Abstract: Objective. To test the usefulness and cost savings resulting from application of the new American College of Rheumatology (ACR) guidelines for assessing the risk for the development of clinically significant liver disease in rheumatoid arthritis (RA) patients treated with methotrexate (MTX).Methods. One‐hundred twelve MTX‐treated RA patients were prospectively followed up for MTX hepatotoxicity and underwent liver biopsies according to modified guidelines of the Psoriatic Task Force (PTF). All biopsies were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 15 publications
0
32
0
2
Order By: Relevance
“…renal organic anion transporter; drug elimination; nephrotoxicity AMONG THE VARIOUS DRUGS in use for the treatment of malignancies, the group of antimetabolites is of significant practical relevance. The antifolate methotrexate (Mtx) is also successfully used in various nononcological indications like rheumatoid arthritis and psoriasis (6,8,19,23,33). However, chemotherapy with Mtx is confronted with adverse effects such as bone marrow suppression, hepatotoxicity, as well as acute and long-term nephrotoxicity.…”
mentioning
confidence: 99%
“…renal organic anion transporter; drug elimination; nephrotoxicity AMONG THE VARIOUS DRUGS in use for the treatment of malignancies, the group of antimetabolites is of significant practical relevance. The antifolate methotrexate (Mtx) is also successfully used in various nononcological indications like rheumatoid arthritis and psoriasis (6,8,19,23,33). However, chemotherapy with Mtx is confronted with adverse effects such as bone marrow suppression, hepatotoxicity, as well as acute and long-term nephrotoxicity.…”
mentioning
confidence: 99%
“…Although one study showed transaminase elevations higher than twice the upper limit of normal in 13% of patients [111] , another report assessing 6000 patients receiving MTX, transaminase elevation was described in only 0.6% of patients [112] . Despite this wide difference, most studies concluded that prolonged use of low-dose MTX monotherapy (10 mg/wk for 2-15 years) has favorable longterm safety, and that the development of significant liver fibrosis and cirrhosis is very low [113] ; rather, steatosis was the main finding when biopsies were carried out for surveillance dictated by cumulative MTX dose ( Figure 2) [114] .…”
Section: Association Of Sle With Drug-induced Hepatotoxicitymentioning
confidence: 95%
“…462 However, adherence to only blood tests can still miss an occasional patient with advance liver disease. 464 In sarcoidosis, 100 liver biopsies were performed in 57 patients after each 1 to 1.5 g of accumulated doses. Fourteen patients had changes consistent with methotrexate toxicity (47 had changes due to sarcoidosis).…”
Section: Methotrexatementioning
confidence: 99%